The Geopolitics of The Natuna Sea and Indonesia's Defense Challenges - Lestari, Amin; Soemantri, Asep Iwa; Setiawati, Deni; Prakoso, Lukman Yudho; Risahdi , Muhammad (Jurnal Indonesia Sosial Sains, 2025)
The Natuna Sea is a strategic area of Indonesia that borders directly on the South China Sea, making it an important point in regional geopolitics. This research aims to analyze the geopolitical dynamics of the Natuna Sea, national defense challenges, and maritime threat mitigation strategies. The research method uses a descriptive qualitative approach with document studies, secondary data, and interviews with defense experts. The results of the study show an increase in foreign ship activity, piracy, and the potential for cross-border conflicts that threaten sovereignty. These findings underscore the need for defense capacity building, technological integration, and proactive maritime diplomacy. This research provides policy recommendations to strengthen the sovereignty and security of the Natuna Sea.